DISTRIBUTION PATTERNS OF LITHOGENIC AND ANTHROPOGENIC COMPONENTS IN LAKE LIMBOTO SEDIMENT BASED ON MAGNETISM PARAMETERS AND GEOCHEMISTRY - YUNGINGER - NIM: 32315001, RAGHEL
Lake Limboto is one of the lakes in Sulawesi, Indonesia, which is currently experiencing serious degradation with an intensive sedimentation rate. The pressure of population increasingly living around the lake, resulting in sedimentation in Lake Limboto increases, no longer only derived from lithogenic contributions but also by anthropogenic components. In this study, the lithogenic and anthropogenic components in surface sediments from 17 points in the lake were studied and identified using a combination of magnetic and geochemical analyses. The results showed that although the value of magnetic susceptibility in R (Residential) and NR (Non-Residential) areas were relatively similar, but the value of saturation isothermal remanent magnetization (SIRM) as well as SIRM/χLF differed significantly, implying that the magnetic mineral characteristics in the R areas are more controlled by anthropogenic components, whereas in the NR area is controlled by the lithogenic component. Furthermore, the discrepancy between the contribution of anthropogenic and lithogenic components supported by abundance of heavy metals and rare earth element (REE). Sediment samples in the R area contained higher concentrations of Mn, La, Pr, and Gd, while in the NR areas higher concentrations of Fe, Sc, Nd, and Ce. In the NR area, the magnetic parameters correlate well with the heavy metal Fe (r = 0.91), Cu (r = 0.92), Mn (r = 0.84), and Zn (r = 0.65) n = 6, indicates that the source of the magnetic mineral in the NR area equal to that of a heavy metal component lithogenic. However, a similar correlation was not observed in the R area, reflects the variation of anthropogenic component resources in this area. The results of this study demonstrate that combinations of magnetic and geochemical analysis can distinguish lithogenic and anthropogenic components in surface sediments of Lake Limboto.